PLAGIOCLASE PREFERRED ORIENTATION BY TOF NEUTRON DIFFRACTION AND SEM-EBSD - Xie Y.; Wenk H.-R.; Matthies S. (My University, 2003)
The lattice preferred orientation (LPO) of an anorthosite (composed of andesine) sampled from a highly deformed anorthositic mylonite (Grenville Province, Quebec) was measured by TOF neutron diffraction and SEM-EBSD. The quantitative texture analysis of neutron data was accomplished by using the Rietveld texture analysis with the WIMV algorithm, implemented in the program package Materials Analysis Using Diffraction (MAUD). The texture calculations of the EBSD data were performed by using the program BEARTEX. Analyses from neutron and electron diffraction data gave similar results if EBSD data are smoothed to account for grain statistics. The principal pole figures show (010) roughly parallel to the rock foliation, (001) poles exhibiting a low angle (∼25°) to the pole to foliation, and (100) poles close to the Y-direction (perpendicular to the lineation and foliation pole). The [100] crystallographic direction shows a maximum in the lineation direction, [010] directions concentrate near the foliation pole. The geological deformation conditions and the constructed pole figure patterns indicate that the preferred orientation could be attributed to intracrystalline slip dominantly on (010) with [100] as slip direction. Elastic properties, calculated by averaging, document weak anisotropy that has implications for the seismic structure of the lower crust.
Keywords: Plagioclase texture; Rietveld analysis; EBSD; Seismic anisotropy